Intrinsic Alu affects for RNA splicing in a minigene model - Mina Nakama; Bunta Imanaka; Yuma Kimoto (Biochemistry and Biophysics Reports)
Alu elements are commonly located in the introns of primate genomes and, once transcribed, can alter splicing patterns. The insertion of an antisense Alu element into intron 9 was shown to enhance exon 10 skipping in a previously developed ACAT1 minigene model including exon 9–exon 11. This study investigates two intrinsic original Alus' role located in the intron in ACAT1 sequence using the same minigene splicing system. The deletion of intrinsic full AluSx originally located in intron 10 resulted in intron 10 retention, whereas the partial AluJb or antisense AluSx in the same intron was not sufficient for this process. Even normal splicing transcript wasn't shown without intrinsic full AluSx. Exon skipping was induced under the condition in which the intronic splice out prior to. Also, exon skipping was required with two close Alu elements with inverse orientations such as head-to-head and tail-to-tail in our minigene model. Intron retention seems to have been affected by shortening of introns or deletion of Alu's splicing regulatory elements. Either way, Alus are associated with human gene expression incorporating themself and adopting in the human genome splicing system.